Focal Point on Billboard Juicenation - Nasruddin, Merlina Fatimah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Juicenation is a commercial products of electric liquid vaporizer that carries the theme and taste of fruit in its commercial advertisements. One of them appeared on Billboard on Jalan Terusan Jakarta, Bandung city. The purpose of this study is to identify the focal point element in the visualization of the Juicenation Billboard advertisement as the element that most attracts the audience’s eye. This research method uses a quantitative approach by distributing questionnaires to a number of respondents to identified which elements that attractive the most. There is an arrow shape element that represents the formal form of the product, typography, the color of the Juicenation product variant itself and the fruit element, which both of them appear dominant.